DETERMINATION OF DEPENDENCE OF ENERGY STEALTH COEFFICIENT OF SATELLITE COMMUNICATION SYSTEMS AT SIGNAL DETECTION FROM CHOICE OF OPERATING FREQUENCY ON THE BASIS OF NUMERICAL METHODS FOR SOLVING NONLINEAR EQUATIONS - Alexey Vladimirovidi Lyakhov (Современная наука и инновации, 2022)
In the article on the basis of results of signal detection in a channel with the Rician fading, analysis of depth of fadings in a transionospheric radio channel and numerical methods of solving nonlinear equations, developed a methodology of estimation of energy stealth coefficient in satellite communications systems depending on the choice of operating frequency.